Association pattern of reciprocal translocations induced by chemicals and ionizing radiation in mouse germ cells: a comparison between single and combined treatments - de Luca, Julio Cesar (2011)
The similarity degree of chemical, ionizing radiation, and combined treatments of chemical plus ionizing radiation in their capacity to induce reciprocal translocations was analyzed by means of multivariate analysis techniques on mice germ cells. The effect of three different doses of gamma rays, four doses of X-rays, and different doses of adriamycin, mitomycin C, thio-tepa and bleomycin, as well as the combined treatments of two doses of gamma rays with adriamycin, mitomycin c and thio-tepa, were studied. Our objectives were: 1) to determine the degree of similarity between the effects of chemicals and ionizing radiations in relation to the induction of reciprocal translocations in germ cells; and 2) to test the conclusions reached by previous authors using only single treatments. Data were arranged in a basic data matrix, analyzed by cluster analysis and ordination methods. The results showed that: 1) as single and combined treatments were grouped together, there was not a specifc pattern of chromosomal aberration induced for physical and chemical agents; 2) the association degree between single treatments was similar to that obtained by previous authors, although in this analysis combined treatments were added; and 3) some combined treatments using 9 Gy and drugs appear in different groups, although we expected that all the combined treatments of drugs with 9 Gy were grouped together. As a working hypothesis, we propose that the variability observed when the different treatments were compared could be dose dependent.